Salivary immunoendocrine and self-report monitoring profiles across an elite-level professional football season - Springham, M.; Williams, S.; Waldron, M.; Strudwick, A. J.; Mclellan, C.; Newton, R. U. (Medicine & Science in Sports & Exercise, 2021)
Purpose This investigation examined the longitudinal changes and interrelationships of salivary and self-report monitoring measures across a professional football season.